Modulated synthesis of thiol-functionalized fcu and hcp UiO-66(Zr) for the removal of silver(i) ions from water. Issue 2 (12th January 2021) - Moll, Bastian; Müller, Tim; Schlüsener, Carsten; Schmitz, Alexa; Brandt, Philipp; Öztürk, Secil; Janiak, Christoph
Abstract : Mercaptoacetate modulation represents an easy way of introducing thiol groups into UiO-MOFs for enhanced uptake of Ag + from aqueous solutions. Abstract : In recent years there has been a developing interest in the capture of Ag(i ) ions from wastewater. In this work we present the synthesis and characterization of two modified thiol-containing UiO-66 metal–organic frameworks (MOFs) capable of removing Ag(i ) from aqueous solution. Mercaptoacetic acid (HMAc) was used as a modifier and incorporated as mercaptoacetate into the MOFs. The modulation of the UiO-66 synthesis with HMAc represents an easy and low-cost method for the introduction of thiol groups into the UiO-66 framework, while preserving the general UiO-66 properties like porosity and stability. The usage of very high equivalents of HMAc in relation to ZrCl4 led to reproducible formation of the rare hexagonal close packed (hcp ) topology of UiO-66 instead of its common face-centered cubic (fcu ) packing. The materials showed a maximum uptake for Ag(i ) from aqueous solutions of over 84 mg g −1 for the fcu structure and 36 mg g −1 for the hcp structure. The uptake follows a Langmuir type behavior for both topologies. Uptake kinetics indicates a pseudo second-order rate law for the initial uptake before diffusion control takes over.